An Analysis of Capital and Pricing in Supporting Business Sustainability of Traditional Market Traders in Sudimampir, Banjarmasin - Hikmahwati Hikmahwati; Nabila Almaida; Naylia Nikmah (Sultan Publisher, 2025)
This study was conducted to examine the influence of business capital and pricing on the sustainability of traders operating in Sudimampir Market, Banjarmasin. The background of the research highlights the importance of financial strength and price competitiveness as key factors in ensuring the long-term viability of small traders in traditional markets. The study aims to determine whether these two variables capital and price significantly affect business sustainability. A quantitative approach with a causal associative method was applied, involving 40 traders as respondents. Data were analysed using multiple linear regression with SPSS version 22. The results show that both business capital and price have a positive and significant effect on business sustainability. Specifically, the significance values for capital and price were 0.034 and 0.001 respectively, indicating strong statistical relevance. The coefficient of determination (R²) was 0.357, meaning 35.7% of the variation in business sustainability can be explained by the two variables. The study contributes to the field by reinforcing the role of capital and pricing strategies in sustaining micro-enterprises and offers practical insights for traders and policymakers seeking to support traditional markets.